Perspectives of Bradyrhizobium and Bacillus Inoculation for Improvement of Soybean Tolerance to Water Deficit - Jelena Marinković; Dragana Miljaković; Vuk Đorđević; Marjana Vasiljević; Gordana Tamindžić; Jegor Miladinović; Sanja Vasiljević (Agronomy)
The objective of this study was to analyze the response of antioxidant parameters in soybean plants inoculated with newly isolated Bradyrhizobium japonicum and Bacillus subtilis strains as single and co-inoculants under drought stress. Bacterial strains were selected according to osmotic stress tolerance (in the presence of 36% PEG 6000) in appropriate liquid media. The effect of soybean inoculation was examined in a soil pot experiment in water deficit conditions (0 and 7 days withholding water). The influence of water stress and inoculation was evaluated in soybean leaves, roots, and nodules through guaiacol peroxidase (POX), ionically cell-wall-bound peroxidase (POD) activity, and ABTS˙+ radical cation scavenging capacity, as well as parameters of N-fixation efficiency. The results showed a significant influence of inoculation on constitutive and drought-induced antioxidant and N-fixation parameters. Inoculation increased the activity of POX (up to 116, 169, and 245%), POD (up to 116, 102, and 159%), and antioxidant capacity (up to 74, 76, and 81%) in soybean leaves, roots, and nodules under water deficit, respectively. Application of bacterial strains resulted in higher shoot, root, and nodule weight and nitrogen content both in non-stressed and drought stress conditions. Overall, co-inoculation had better effects on the investigated soybean parameters compared to single inoculation. Selection and application of bacterial strains with improved tolerance to drought stress is necessary in developing inoculants that would result in enhanced crop production under unfavorable environmental conditions.